P516 Discrete choice experiment to examine patient preferences for surgical interventions in patients with Crohn's perianal fistulas: results from a global burden of illness study. (21st January 2022) - Karki, C; Athavale, A; Hantsbarger, G; Lee, K; Milicevic, S; Perovic, M; Raven, L; Sajak-Szczerba, M; Abilash, V; Tozer, P
Abstract: Background: Perianal fistulas (PAF) are a common complication of Crohn's disease (CD) and patients with Crohn's perianal fistulas (CPF) experience low health-related quality of life and a higher burden of symptoms than patients with CD without PAF (non-PAF CD). Treatment options for PAF, including medical and surgical interventions, are associated with high rates of relapse or failure. This global study assessed the burden of illness in patients with CPF compared with patients with non-PAF CD. Here, we present data on patient satisfaction with currently available PAF treatments and the attributes that drive treatment choice for patients with CPF. Methods: This cross-sectional study was conducted in seven countries (France, Germany, Spain, UK, Canada, Australia and Japan) in patients aged ≥21 and ≤90 years with self-reported physician-diagnosed CD. Patients were classified as non-PAF CD (cohort 1) or CPF without PAF-related surgery (cohort 2) or CPF with PAF-related surgery (cohort 3). Using a web-enabled questionnaire, patient satisfaction with current PAF treatment options was recorded using a 1–9 scale and relative treatment attribute preferences were assessed via a discrete choice experiment (DCE) that included six attributes (Figure 1). Patients evaluated two treatment profiles at a time ("choice tasks") to identify their most preferred treatment of the choices available. Data were analysed using descriptive statistics. Results: A total of 929 patients were recruited, 620 with non-PAF CD and 309 with CPF. Of those with CPF (cohort 2, n=174; cohort 3, n=135), 68% were male, 65% were aged 21–40 years and 83% were currently taking CD-related medication. The median number of PAF was the same in cohorts 2 and 3 (both 2.0), although cohort 3 had a higher proportion of patients with active PAF (119/135 [88%]) compared with cohort 2 (136/174 [78%]; p =0.022). In cohort 3, 105/135 (78%) patients had ≥3 PAF-related procedures/surgeries, and ≥1 and >3 post-operative complications were experienced by 117/135 (87%) and 34/135 (25%) patients, respectively. Mean satisfaction scores were moderate for the majority of PAF treatment options and similar in both cohorts (range 6.2–6.9), although cohort 3 had significantly less satisfaction with long-term seton placement than cohort 2 (6.2 vs 6.7, respectively; p =0.035). Among the tested attributes, post-operative discomfort and fistula healing rate were the most important attributes influencing treatment choice (Figure 1). Conclusion: In this study, patients with CPF had moderate satisfaction with PAF treatment options, regardless of surgical intervention. The DCE demonstrated that patients preferred interventions with better healing rates and lower post-operative discomfort compared to other attributes tested.